Laparoscopic Nephrectomy in Benign Renal Diseases- A Tertiary Hospital Experience - Muhammad Mansoor Yaqoob; Arif Ali; Suhail Dilawar; Shahzad Ali; Saeed Ahmed Khan; Shahid Hussain (KARACHI MEDICAL AND DENTAL COLLEGE, 2021)
ABSTRACT:    Objectives:  The purpose of our study is to share experience of performing simple laparoscopic nephrectomy in benign cases.   Study Design: Descriptive study.    Place & Duration of Study:    Department of Urology, Jinnah Postgraduate Medical Center (JPMC) Karachi, between Jan 2015 to Dec 2019 with minimal one and half year follow-up.   Methodology: Our inclusion criteria were benign symptomatic nonfunctioning kidneys requiring nephrectomy. Laparoscopic nephrectomy was performed under general anesthesia with oblique position with three or four port technique was used. The demographic data, operative and post- operative details were carefully noticed and recorded in SPSS software version 20.    Results: Total 40 patients were included in the study. Twenty four were females and 16 were males. Age ranges from 20 to 62 years with mean age of 44.64 + 11.04 years. Left sided were 24 patients (60%) while the right sided in 16(40%). Flank pain was the most common presenting complaint seen in 92.50% patients. Renal stone disease representing the most common indication for nephrectomy (40%) followed by ureteric stone (22.5%), chronic pyelonephritis (17.5%) and PUJO (15%). Our mean operative time was 200.29+47.98. Six patients (15%) were converted to open surgery because of intraoperative complications in 10% of patients including hilar vascular injury and gut injury and failure to progression in two (5%). Among the post- operative complications, early included low grade fever (10%) and wound infection (7.5%) while late included port site hernia (5%) and abscess at renal bed (2.5%). Chronic pyelonephritis was the most common histopathological report representing 45% of total cases. Our success rate was 85%.   Conclusion: The role of laparoscopic nephrectomy in benign non-functioning kidneys is a better alternate to open nephrectomy in terms of pain, post-operative recovery and cosmetic results. The operative time and conversion rate can minimize after passing through adequate learning time and experience